2014
DOI: 10.1159/000356367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of Prostate-Specific Antigen as an Instrument for Early Detection of Prostate Cancer beyond Urologists: Results of a Representative Cross-Sectional Questionnaire Study of General Practitioners and Internal Specialists

Abstract: Objectives: The aim of this cross-sectional study was to evaluate the value of prostate-specific antigen (PSA) testing as a tool for early detection of prostate cancer (PCa) applied by general practitioners (GPs) and internal specialists (ISs) as well as to assess criteria leading to the application of PSA-based early PCa detection. Methods: Between May and December 2012, a questionnaire containing 16 items was sent to 600 GPs and ISs in the federal state Brandenburg and in Berlin (Germany). The independent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Brazilian GP tend to start screening earlier at the age of 40 (21.5%), only 32% starting at age 50 which is unlike the 73% of Canadian family physicians . Approximately 1.9% of GP begin the process before 40 years of age which is very similar to the findings pertaining the German GP (1.8%) . In our study, the percentage of those who started PCS in men without risk factors of ages 40 to 49 years (45%) was similar to the findings of Kim et al (51%) .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Brazilian GP tend to start screening earlier at the age of 40 (21.5%), only 32% starting at age 50 which is unlike the 73% of Canadian family physicians . Approximately 1.9% of GP begin the process before 40 years of age which is very similar to the findings pertaining the German GP (1.8%) . In our study, the percentage of those who started PCS in men without risk factors of ages 40 to 49 years (45%) was similar to the findings of Kim et al (51%) .…”
Section: Discussionsupporting
confidence: 87%
“…11 Regarding the ages to start and end the screening, the data from this study are similar to those found by others, with the majority of physicians indicating the onset at 40 to 50 years of age, and ending by ages 70 to 80 years. 18,21,22 Brazilian GP tend to start screening earlier at the age of 40 (21.5%), only 32% starting at age 50 which is unlike the 73% of Canadian family physicians. 21 Approximately 1.9% of GP begin the process before 40 years of age which is very similar to the findings pertaining the German GP (1.8%).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The increasing use of Prostate-specific antigen (PSA) testing [1] has led to frequent detection of small, well-differentiated, very low-risk prostate cancer (PCa) foci that might never become harmful in a man‘s lifetime and therefore have to be considered overdiagnosed [2]. Active surveillance (AS) providing the ability to stratify treatment according to dynamic progression criteria over time has therefore been adopted into clinical practice in order to minimize unnecessary treatment.…”
Section: Introductionmentioning
confidence: 99%